An assessment of syndicalist movements in turkey and the presentation in the press: The sample case of the strike decision of hava-iş union - (:unkn) unknown (My University, 2011)
After the process of the newly transformation in the structures of production and by the reconstruction of capitalism, the new right politics has been determinative in the disorganization of the working class. The new production flexibilities in manufacturing, have not only made new forms of exploitations arisen, but also aff ected the labor organizations deeply. In this context, the strike decision taken on July 20th, 2007 and applied by the Civil Aviation Union of Turkey (Hava-Iş) has been assumed to be as a sample significant resistance against new right politics that had been opposed by the labor who didn't accept to lose their employee personal rights. In this work, the presentation of the strike initiative of Hava-Iş in Turkish press has been taken as the main problematic of the essay and the context of the mission committ ed by mass media, which has been used as the legitimating space of the new right politics. Additionally, our aim was to find out what kind of discourse has been used for the issue of the construction of news and also the issue of structural bias in the news has been intended by examining the journals representing the Turkish press which are as follows: Cumhuriyet, Hürriyet and Yeni Şafak. The general presupposition of this work was given such as the media in Turkey develops a discourse in favor of the employers about the trade union movements and strikes, and that it contributes to the dominant ideology about the working life organized by the new right policy in order to orient the workers to contribute to this social reproduction. In fact, taking in consideration the principal views and applications of A. Teun van Dijk, the critical discourse analysis model has been utilized in this essay.